Daily Behavior of Sambar Deer (Cervus Unicolor) within Ex-Situ Conservation Areas in Deer Parks - Evi Apriana; Roslina; Lukmanul Hakim; Armi; Nurlena Andalia (Jurnal Penelitian Pendidikan IPA, 2023)
Research has been conducted on "Daily Behavior of Sambar Deer (Cervus unicolor) in Ex-situ Conservation Area in Deer Park, Desa Lamtanjong, Kabupaten Aceh Besar". This study aims to determine the daily behavior of sambar deer in the conservation area in deer park Desa Lamtanjong, Kabupaten Aceh Besar, and the most dominant behavior carried out by sambar deer, as well as the feasibility of the results of research on the daily behavior of sambar deer (Cervus unicolor) in Deer park Desa Lamtanjong, Kabupaten Aceh Besar. The approach used in this study is quantitative, the type of research used is descriptive. The sample in this study was 6 sambar deer consisting of 2 males and 4 females. Data on the daily behavior of sambar deer were obtained through direct observation using the animal sampling scan method for 14 days of observation. Based on the results of the study, it is known that the behavior carried out is in the form of eating behavior, shifting behavior, resting behavior, grooming behavior, and reproduction. The dominant behaviors were eating (47%), moving (20%), resting (29%), grooming (3%), and reproduction (1%). The dominant behavior that deer perform is feeding behavior. The use of the results of this research is applied in the form of a practicum guide for the Animal Ecology course, to conduct practicum directly at the deer park Desa Lamtanjong, Kabupaten Aceh Besar.